2003
DOI: 10.1002/cncr.11152
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor, CD68, and epidermal growth factor receptor expression and survival in patients with Stage II and Stage III colon carcinoma

Abstract: BACKGROUNDThe elucidation of new therapeutic targets of prognostic significance in colon carcinoma is necessary to improve outcomes. In the current study, the authors examined the expression of epidermal growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) in primary colon carcinoma cases and VEGF in tumor‐associated macrophages (TAM)/stroma, and their correlation with survival.METHODSThe authors identified 131 consecutive American Joint Committee on Cancer Stage II and Stage III colon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 36 publications
6
92
2
4
Order By: Relevance
“…In a series of studies, overexpression of VEGF was detected in 45% to 70% of CRCs [21] [35]- [42] which is comparable with the present study. However, Khorana et al reported lower incidence of VEGF immunopositivity (34%) [43] whereas Uner et al showed higher frequency of 86% in CRCs [44]. In the present study, a significant association was observed between VEGF expression and high histological grade tumors.…”
Section: Discussioncontrasting
confidence: 49%
“…In a series of studies, overexpression of VEGF was detected in 45% to 70% of CRCs [21] [35]- [42] which is comparable with the present study. However, Khorana et al reported lower incidence of VEGF immunopositivity (34%) [43] whereas Uner et al showed higher frequency of 86% in CRCs [44]. In the present study, a significant association was observed between VEGF expression and high histological grade tumors.…”
Section: Discussioncontrasting
confidence: 49%
“…[12][13][14] Some studies relying on immunohistochemical staining of human colorectal cancers, in fact, indicate that macrophages along the tumor margin [31][32][33] and macrophages expressing VEGF 34 are associated with a good prognosis. Others have suggested that macrophages in colorectal cancer may have co-stimulatory functions in antitumor immunity 35 or may be able to induce tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Recent studies have described a significant association between increased protein levels of EGFR and poor prognosis in patients with CRC. 31,32 However, whether EGFR is a predictive factor, as well as being a prognostic factor, is still unclear. Ling et al showed that in human cervical squamous cancer cells, high EGFR protein expression levels are associated with a greater sensitivity to Topo 1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%